A teoria econômica do crime: uma revisão de literatura sobre a relação das variáveis socioeconômicas com a criminalidade no Brasil - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Crime is considered a social problem worldwide. In addition to affecting public safety, it also harms the economy. The Economic Theory of Crime, developed by Gary Becker in 1968, elucidates the behavior of the criminal in order to justify his criminal actions. Within the theory created by Becker and expanded by Isaac Ehrlich, we seek to find a relationship between crime and socioeconomic variables. The largest country in Latin America, Brazil, suffers from crime rates in its strongholds, where it recorded 57,956 homicides in 2018, 27.8 deaths per 100,000 inhabitants. Therefore, the present study has the general objective of analyzing the influence of socioeconomic indicators on crime in Brazil. To achieve this objective, a bibliographic research was carried out within the area of ​​crime related to socioeconomic variables, having as an approach the relationship between crime and the level of income, education and unemployment. In order to verify if there is a relationship between the variables, a synthesis was prepared on the research found in the works addressed and, in general, descriptive statistics were used to prove the hypotheses. From the synthesis exercised, it was found that higher income levels negatively influence crime; higher levels of education also negatively influence crime; and, in most analyses, higher levels of unemployment positively influence crime. Therefore, this work aims to contribute to the analysis of public security in the country, in order to identify the relationship between crime and socioeconomic variables within Brazil.
The economic theory of crime: a literature review on the relationship between socioeconomic variables and crime in Brazil
Keywords: Teoria econômica do crime; Variáveis socioeconômicas; Criminalidade; Economic theory of crime; Socioeconomic variables; Criminality; CNPQ::CIENCIAS SOCIAIS APLICADAS